PENILAIAN ESTETIKA AKSESORIS KALUNG BERBAHAN DASAR POLYMER CLAY - Chairat, Yunia; Noerharyono, Muchamad; Suliyanthini, Dewi; Radiona, Vivi (Practice of Fashion and Textile Education Journal, 2023)
This study aims to make necklace accessories products made from polymer clay which are then assessed by expert panelists based on the application of design elements, namely from the aspects of shape elements, color elements, and texture elements. Meanwhile, the application of design principles is from the aspects of the principle of harmony, the principle of proportion, and the principle of rhythm. The method used is descriptive quantitative, with a pre- experimental design, a one-shot case study model, and an experiment in the form of 5 necklace accessories products made from polymer clay inspired by the shape of the embroidery soutache technique with the type of princess necklace. The research data was obtained from an assessment instrument given to 5 expert panelists, and the assessment was measured using a graded rating scale with a scale of 1-4. The results of the study from the design element indicator got a score of 3,448 with a percentage value of 86.2% included in the excellent category. Meanwhile, the design principle indicator got a value of 3.34 with a percentage value of 83.5% included in the excellent category. The overall result of getting a score of 3.38 and apercentage value of 84.5% indicates that the necklace accessories are close to the scale very well. The highest final value based on the design of necklace accessories obtained the 3rd design with an excellent value of 88.69%, while the lowest value was obtained by the 2nd necklace accessories design with a value of 80.9%.